THE INFLUENCE FACTORS OF PURCHASING DECISION “BUDI UTOMO” TARO STICK IN PONTIANAK - Nur Jannah; Eva Dolorosa; Imelda Imelda (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACTThe high competition requires snack producers to be more active in implementing marketing strategies so that the product may sells in the market. The purpose of this study is to find out the factors influence consumers decision for purchasing “Budi Utomo” taro stick in Pontianak. This research used survey method with qualitative and quantitative data type. Total sample of this research was 100 respondents. The data analysis technique used is factor analysis. The result of this research shows that there are six factors affecting the consumers in purchasing decision, namely price, family, product, promotion, location, and individual. The most dominant factors “price”.Key Word: Factors analysis, purchasing decisions, taro stick, consumer behavior